2016
DOI: 10.1111/epi.13334
|View full text |Cite
|
Sign up to set email alerts
|

Progression of gray matter atrophy in seizure‐free patients with temporal lobe epilepsy

Abstract: SUMMARYObjectives: To investigate the presence and progression of gray matter (GM) reduction in seizure-free patients with temporal lobe epilepsy (TLE). Methods: We enrolled 39 consecutive TLE patients, seizure-free for at least 2 years-20 with magnetic resonance imaging (MRI) signs of hippocampal sclerosis (TLE-HS), 19 with normal MRI (TLE-NL), and 74 healthy controls. For longitudinal analysis, we included individuals who had a second MRI with minimum interval of 18 months: 21 patients (10 TLE-HS, 11 TLE-NL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
56
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 28 publications
14
56
1
4
Order By: Relevance
“…Labate et al observed GM decreases in the thalami of patients with hippocampal sclerosis and normal MRI with mild TLE (Labate et al, 2008, Labate et al, 2010). In a longitudinal MRI follow-up study of seizure-free TLE patients, Alvim and her colleagues not only found diffuse extrahippocampal GM atrophy but also clarified the progression of the GM atrophy (Alvim et al, 2016). Kim et al found a negative correlation between the disease duration and the thalamocortical FC strength of the bilateral medial prefrontal cortex in patients with IGEs (Kim et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Labate et al observed GM decreases in the thalami of patients with hippocampal sclerosis and normal MRI with mild TLE (Labate et al, 2008, Labate et al, 2010). In a longitudinal MRI follow-up study of seizure-free TLE patients, Alvim and her colleagues not only found diffuse extrahippocampal GM atrophy but also clarified the progression of the GM atrophy (Alvim et al, 2016). Kim et al found a negative correlation between the disease duration and the thalamocortical FC strength of the bilateral medial prefrontal cortex in patients with IGEs (Kim et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…11 This result is in line with a previous study demonstrating the progression of diffuse extrahippocampal gray matter atrophy in temporal lobe epilepsy patients with and without hippocampal sclerosis. 27 Interestingly, we newly found that the characteristic path length was the first network measure of alteration, even in the patients with newly diagnosed epilepsy who were in a drug-naïve state. The characteristic path length is the average shortest path length between all nodes as a measurement of global connectivity and network integration, 2,16 and the mean clustering coefficient measures the connection density in local sub-networks surrounding a given node related to the local network efficiency and segregation, which was decreased in the patients with chronic epilepsy.…”
Section: It Alsomentioning
confidence: 97%
“…These include problems with executive function, cognitive processing, concentration, and social recognition . Furthermore, mTLE patients demonstrate diffuse neocortical hypometabolism, numerous brain connectivity perturbations, and multifocal gray matter atrophy . In one study using voxel‐based morphometry analysis of serial magnetic resonance imaging (MRI) scans in mTLE patients, gray matter reduction was noted not only in limbic structures, but also in frontal, parietal, and occipital cortices, as well as bilateral thalamus (Figure ) .…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Furthermore, mTLE patients demonstrate diffuse neocortical hypometabolism, numerous brain connectivity perturbations, and multifocal gray matter atrophy. 3,13,14 In one study using voxel-based morphometry analysis of serial magnetic resonance imaging (MRI) scans in mTLE patients, gray matter reduction was noted not only in limbic structures, but also in frontal, parietal, and occipital cortices, as well as bilateral thalamus (Figure 1). 15 These observations may suggest a common subcortical source (or sources) of widespread network dysfunction in mTLE.…”
mentioning
confidence: 99%